2015
DOI: 10.1007/s12192-014-0531-6
|View full text |Cite
|
Sign up to set email alerts
|

A role for the Parkinson’s disease protein DJ-1 as a chaperone and antioxidant in the anhydrobiotic nematode Panagrolaimus superbus

Abstract: Mutations in the human DJ-1/PARK7 gene are associated with familial Parkinson's disease. DJ-1 belongs to a large, functionally diverse family with homologues in all biological kingdoms. Several activities have been demonstrated for DJ-1: an antioxidant protein, a redoxregulated molecular chaperone and a modulator of multiple cellular signalling pathways. The majority of functional studies have focussed on human DJ-1 (hDJ-1), but studies on DJ-1 homologues in Drosophila melanogaster, Caenorhabditis elegans, Dug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…Organisms have developed adaptive mechanisms for cellular detoxification, including systems that repair or prevent damage caused by oxidants ( Michiels et al ., 1994 ). Among such defense systems in the anhydrobiotic nematode Panagrolaimus superbus are: protein DJ-1 ( Culleton et al , 2015 ), glutathione peroxidases (GP114) and peroxiredoxin (PER).…”
Section: Introductionmentioning
confidence: 99%
“…Organisms have developed adaptive mechanisms for cellular detoxification, including systems that repair or prevent damage caused by oxidants ( Michiels et al ., 1994 ). Among such defense systems in the anhydrobiotic nematode Panagrolaimus superbus are: protein DJ-1 ( Culleton et al , 2015 ), glutathione peroxidases (GP114) and peroxiredoxin (PER).…”
Section: Introductionmentioning
confidence: 99%
“…DJ-1 was first identified as an oncogene (2) and has since been described as a causative gene for early-onset Parkinson disease (3,4). Although DJ-1 has protease (5-7) or chaperone (8,9) activities, most studies have focused on its protective role against oxidative stress (10 -15). Knock-out of the DJ-1 gene enhances hydrogen peroxide (H 2 O 2 ) and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-mediated cell death.…”
mentioning
confidence: 99%
“…Remarkably, we observed that the thermostability of AtDJ-1B increases upon oxidation, which indicates that the oxidized form of AtDJ-1B is more likely than reduced AtDJ-1B to retain its chaperone activity under sustained heat stress. Other DJ-1 family members have also been shown to be highly thermostable, with a T M values ranging from 64 to 77 °C [36,51,52]. Here, we determined a comparatively lower T M for AtDJ-1B of 59.7 °C, and observe an increase in T M of approximately 8–10 °C for oxidized AtDJ-1B.…”
Section: Discussionmentioning
confidence: 50%